IDENTIFIKASI PERMUKIMAN KUMUH DALAM KAWASAN PELABUHAN DI KELURAHAN PELAMBUAN KECAMATAN BANJARMASIN BARAT - Hafifah, Nur; Achmad Priyadharma, Andi (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
This study aims to identify the conditions and characteristics of slum settlements located in the port area of Pelambuan Subdistrict, West Banjarmasin District. The area is characterized by high population density that has developed around port-related economic activities, resulting in pressure on environmental quality and spatial organization of housing. This research is significant because port areas not only function as centers of economic activity but also serve as residential zones for low-income communities who live in environmentally vulnerable conditions with limited basic infrastructure. The study employs a qualitative approach using a case study method. Data were collected through field observations, in-depth interviews, and documentation in five representative areas: RT 29, 41, 43, 59, and 66. Data analysis was conducted using the Miles and Huberman interactive model, which involves data reduction, presentation, and conclusion drawing. The validity of the data was tested through source, technique, and time triangulation, as well as by confirming findings with informants. The results indicate that residential areas in Pelambuan still face serious physical and environmental problems, such as dense semi-permanent housing, narrow neighborhood roads, non-functional drainage systems, and direct disposal of household waste beneath the houses. From a social perspective, the community is dominated by informal sector workers with unstable incomes, which limits their ability to improve housing conditions. However, in several areas, there has been a growing awareness among residents to maintain environmental cleanliness through collective community activities